To Combat White Collar Crimes In Public And Private Sector And Need For Strong Legislation And Ethics: Dr Aftab Ahmad Malik, Engr. Mujtaba Asad ,Waqar Azeem - Malik, Engr. Mujtaba Asad; Malik, Waqar Azeem (International Journal for Electronic Crime Investigation, 2020)
The paper deals with and investigates the requirement of resilient and strong legislation to combat white collar crimes, which are exponentially increasing with time both in public and private sector organizations. The influence of immoral and illegal practices in government, particularly the bribes of the highest order has paralyzed the normal functioning of the financial and legislative organizations. Bank frauds and cybercrimes are also increasing tremendously by employing digital devices and the internet. The purpose of this research is also to investigate the essence of the application of strong laws as well principles of morality and ethics. It is advocated by the authors of this paper that norms of morality and ethics on one hand impact a healthy effect on reducing such crimes but also enhances the productivity and profitability of the organizations in financial terms. Several modern organizations are incorporating and implementing the codes of ethics in professional practices. More strict must be the legislation and Code of Ethics, Ethics is the deterrence force to discourage the wrongdoings and adopting right approach so that honesty prevails and curses, crimes, offenses and sins can be minimized. There a serious need of introducing the social welfare system adopted in Europe, Canada and the USA. The bank employees are involved in Bank frauds and commit offenses of embezzlements and illegal transitions using the computer and other digital devices. The role of business ethics in the banking sector is of immense importance. The malpractices by some politicians must also be noticed with stern and iron hands.